2019
DOI: 10.1213/ane.0000000000003802
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Survey of Female Anesthesiologists’ Childbearing and Parental Leave Experiences

Abstract: While the literature regarding physicians’ childbearing experiences is growing, there are no studies documenting those of anesthesiologists. We surveyed a convenience sample of 72 female anesthesiologists to obtain pilot data. Sixty-six women completed the survey (91.7% response rate), reporting 113 total births from before 1990 to present. Of all birth experiences, proportions of respondents reporting parental leave, lactation facilities, and lactation duration as adequate were 52.3%, 45.2%, and 58.3%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…Various studies have examined parental leave policies in procedural residencies, including anesthesiology [ 10 ], general surgery [ 11 ], orthopedic surgery [ 12 ], and radiation oncology [ 13 ], among others, but there have been no studies focused on pediatric or adult medicine, particularly the subspecialties that involve the longest amount of training: hematology/oncology, cardiology, gastroenterology, and pulmonology/critical care. Our goal was to investigate the state of parental leave policies for such programs and to determine their accessibility to trainees, how consistent they were across programs, and how trainees’ education was impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined parental leave policies in procedural residencies, including anesthesiology [ 10 ], general surgery [ 11 ], orthopedic surgery [ 12 ], and radiation oncology [ 13 ], among others, but there have been no studies focused on pediatric or adult medicine, particularly the subspecialties that involve the longest amount of training: hematology/oncology, cardiology, gastroenterology, and pulmonology/critical care. Our goal was to investigate the state of parental leave policies for such programs and to determine their accessibility to trainees, how consistent they were across programs, and how trainees’ education was impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Practicing physicians in surgery, emergency medicine, and anesthesia have reported receiving limited (and in some cases no) paid coverage for parental leave and often report dissatisfaction with current coverage policies. 10 13 Studies specific to medical residents have found a lack of uniform policies regarding parental leave with regard to funding and also clinical coverage for new parents across several specialty training programs including surgery, OB–GYN, family medicine, and dermatology. 14 17 Trainees often report a perception of stigma and a lack of support for prospective and new parents, both by other trainees and by faculty.…”
Section: Discussionmentioning
confidence: 99%
“…There was considerable heterogeneity in the study populations, survey instruments used and outcomes reported. Most studies included only residents (n=22; 43.1%) 18-40 but 10 included a combination of faculty statuses (19.6%) [41][42][43][44][45][46][47][48][49][50][51] (table 2). Most studies combined participants from different practice disciplines (n=28; 54.9%), 20 -22 27 32 35 36 39 41 42 44 45 50 -66 while the remaining studies reported on participants from a single discipline.…”
Section: Characteristics Of Articles Surveys and Interviewsmentioning
confidence: 99%
“…58 From these studies, examples of harassment and discrimination included receiving a low evaluation referencing the resident’s need to pump, 58 being told that pumping at work indicated that she was less dedicated to her job, 58 and being restricted from pumping during an examination. 43 …”
Section: Characteristics Of Articlesmentioning
confidence: 99%